Construct Validity of the Societal Outreach Scale (SOS). Issue 4 (30th January 2018) - Fike, David S; Denton, Jason; Walk, Matt; Kish, Jennifer; Gorman, Ira
Abstract: Background: The American Physical Therapy Association (APTA) has been working toward a vision of increasing professional focus on societal-level health. However, performance of social responsibility and related behaviors by physical therapists remain relatively poorly integrated into practice. Promoting a focus on societal outreach is necessary for all health care professionals to impact the health of their communities. Objective: The objective was to document the validity of the 14-item Societal Outreach Scale (SOS) for use with practicing physical therapists. Design: This study used a cross-sectional survey. Methods: The SOS was transmitted via email to all therapists who were licensed and practicing in 10 states in the United States that were purposefully selected to assure a broad representation. A sample of 2612 usable responses was received. Factor analysis was applied to assess construct validity of the instrument. Results: Of alternate models, a 3-factor model best demonstrated goodness of fit with the sample data according to conventional indices (standardized root mean squared residual = .03, comparative fit index .96, root mean square error of approximation = .06). The 3 factors measured by the SOS were labeled Societal-Level Health Advocacy, Community Engagement/Social Integration, and Political Engagement. Internal consistency reliability was 0.7 for all factors. The 3-factor SOS demonstrated acceptable validity and reliability. Limitations: Though the sample included a broad representation of physical therapists, this was a single cross-sectional study. Additional confirmatory factor analysis, reliability testing, and word refinement of the tool are warranted. Conclusions: Given the construct validity and reliability of the 3-factor SOS, it is recommended for use as a validated instrument to measure physical therapists' performance of social responsibility and related behaviors.